The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1159/000045728
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme Insertion/Deletion Polymorphism and Prognosis of IgA Nephropathy

Abstract: Background/Aim: Well-known factors for a poor prognosis in IgA nephropathy (IgAN) are hypertension, proteinuria, and renal insufficiency at the time of diagnosis. Also hypertriglyceridemia and hyperuricemia seem to play a role in the progression of IgAN. Angiotensin-converting enzyme (ACE) gene I/D polymorphism has been associated with cardiovascular diseases and with progression of IgAN. We, therefore, investigated the contribution of ACE gene I/D polymorphism in the prognosis of IgAN and its association with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 23 publications
2
22
1
Order By: Relevance
“…Therefore, 6 studies without a second PCR to confirm the DD genotype were also excluded [30,31,32,33,34,35]. Furthermore, 1 study was excluded to avoid inclusion of duplicated data as the same patients and controls seemed to be reported in both studies [16, 36]. Finally, 11 studies with 1,339 IgAN patients and 1,881 controls were used in our meta-analysis, and these studies encompassed 6 Caucasian and 4 Asian subject collections as summarized in table 1[11,12,13,14,15,16,17,18,19,20,21].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, 6 studies without a second PCR to confirm the DD genotype were also excluded [30,31,32,33,34,35]. Furthermore, 1 study was excluded to avoid inclusion of duplicated data as the same patients and controls seemed to be reported in both studies [16, 36]. Finally, 11 studies with 1,339 IgAN patients and 1,881 controls were used in our meta-analysis, and these studies encompassed 6 Caucasian and 4 Asian subject collections as summarized in table 1[11,12,13,14,15,16,17,18,19,20,21].…”
Section: Resultsmentioning
confidence: 99%
“…Studies of IgA nephropathy, mixed glomerular disease and diabetic nephropathy suggest that ACE polymorphisms are more consistently associated with the progression of renal disease. [22][23][24] Indeed, a previous study of LN among Chinese patients demonstrated association of an Alu I/D genotype with progressive renal disease. 21 Previous studies of ACE polymorphisms in renal and cardiovascular disease demonstrate ethnic heterogeneity with stronger associations in non-Caucasian populations similar to those observed in the current study.…”
Section: S44mentioning
confidence: 97%
“…[3] Several studies about the ACE I/D gene polymorphisms in VUR patients have revealed that the D allele might be a risk factor for renal parenchymal damage in children. [7][8][9] Also, the DD genotype has been reported to be associated with reduced renal function in patients with chronic renal diseases like Ig A nephropathy, [10][11][12] focal segmental glomerulosclerosis, [13,14] diabetic nephropathy, [15,16] polycystic kidney disease, [17] and tubulointerstitial nephritis. [18] Because tubulointerstitial damage is also common in VUR, the ACE polymorphism is of interest in this patient group, as it may give clues about the progression of the renal scarring.…”
Section: Introductionmentioning
confidence: 99%